Reliability of adductors/abductors isokinetic testing and its relationship to ice hockey sprint performance - Schaffner, K.; Besson, C.; Gremion, G.; Degache, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction Skating performance is a key parameter of ice hockey performance. Adductors/abductors muscles are highly involved in this locomotion pattern and are poorly investigated in the literature. The aims of this study are: 1) to evaluate the reliability of an adductors/abductors isokinetic test, 2) to compare ice hockey players results to a non-skating sport population, 3) to analyse the relationships between isokinetic test results with off-ice and on-ice tests in elite ice hockey players. Methods In order to evaluate reliability, 12 controls performed two side-lying isokinetic hip tests separated by 6.9 ± 0.7 days. Another group of 9 elite ice hockey players performed an isokinetic hip test 5,6 ± 0.7 days after performance tests (Countermovement jumps, 36.5m off-ice and on-ice sprints). All of the isokinetic tests were analysed with gravity correction. Results The ICC range of the control group were 0.71-0.95, with 75% of the values being above 0.8 (moderate to high) showing a good reliability. The ice hockey players showed a significant difference on adductors isokinetic strength at every speed vs. control group values. No differences were found on the abductors values between the two groups. A significant correlation was found between isokinetic muscle strength of right adductors at 120°/s in concentric and skating time at 36.5 meters (CC: -0.78 / p = 0.01). There is also a relationship between off-ice and on-ice sprints (CC: 0.78; p = 0.005). As well, the vertical jumps and the on-ice sprints were correlated (CC: -0.603; p = 0.05). Discussion Isokinetic hip testing in side-lying position seems to be reliable in a better way than previously described (Emery et al., 1999). Ice hockey players develop significantly higher adductors strength compared to a non-skating sport population, rejoining results from a similar investigation (Kea et al., 2001). Adductors strength seems to be linked with on-ice sprint performance in elite ice hockey players. Finally, there is a relationship between off-ice countermovements jumps and 36.5m sprints with on-ice 36.5m sprint performance, confirming relationships between off-ice and on-ice performance seen in previous studies.